INFLUENCE OF FINANCIAL STRUCTURE ON FINANCIAL PERFORMANCE OF MANUFACTURING FIRMS QUOTED AT NAIROBI SECURITIES EXCHANGE - Kinyua, Mercy Makena Nkirote (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Firms require capital to finance their business operations and invest. Most firms are faced with a predicament on whether to utilize debt or equity to finance their firms. But, firms need to find the best option and effectively manage their risks. The main aim of this study was to determine the influence of financial structure on the financial performance of firms quoted at the Nairobi Securities Exchange. A target population of 8 manufacturing firms quoted at the Nairobi Securities Exchange was considered and a census study was undertaken. A questionnaire was used to collect data from 114 respondents. Secondary data collection form was used for collecting data from the audited financial statements of the eight firms identified for the study as per institution websites and Central Bank of Kenya annual supervisory reports. Data was analyzed using Statistical Package of Social Science (SPSS) version 25. Figures and tables were used to present the results. Pearson Correlation Analysis was used to test the research hypotheses. The study established that debt financing (r =0.767) had a positive linear correlation with the financial performance of manufacturing firms quoted at the NSE. The study concluded that the results are statistically significant and depict a strong relationship as evidenced by the regression coefficients. The finding thus confirms that firms quoted at the NSE rely on debt financing to finance their investment opportunities, which was consistent with the agency theory. The study recommends that the government through Capital Markets Authority (CMA) and other stakeholders in the corporate sector should develop appropriate policies in an attempt to organize the debt capital market to enable the corporate bodies to get access to low cost long term debt capital to finance their investments and operations. Keywords: Financial structure, Financial Performance, Debt Financing.